Grafting Robot - Eid Hamdan; Mohannad aloul; Mazen Qashou; Yazen nader (My University, 2013)
Vegetable grafting has been improved over the last decade, thanks to theIntroduction of new techniques and materials. Grafted seedlings are being progressively adopted by the vegetable industry as propagates of choice for crop establishment. However, despite this recent advance, the percentage of grafted plants in theoverall vegetable production is still relatively low. The high cost of grafting, problemswith soil-born pests and diseases control, and adaptation of the grafted seedlings toa biotic stresses are the major constraints.  All these limiting factors are overviewed and potential ways of remediation